Methane release from pingo-like features across the South Kara Sea shelf, an area of thawing offshore permafrost - Serov, Pavel; Portnov, Aleksei D; Mienert, Jurgen; Semenov, Peter; Ilatovskaya, Polonia (Journal of Geophysical Research: Earth Surface, 2015)
Source at https://doi.org/10.1002/2015JF003467 . The Holocene marine transgression starting at ~19 ka flooded the Arctic shelves driving extensive thawing of terrestrial permafrost. It thereby promoted methanogenesis within sediments, the dissociation of gas hydrates, and the release of formerly trapped gas, with the accumulation in pressure of released methane eventually triggering blowouts through weakened zones in the overlying and thinned permafrost. Here we present a range of geophysical and chemical scenarios for the formation of pingo‐like formations (PLFs) leading to potential blowouts. Specifically, we report on methane anomalies from the South Kara Sea shelf focusing on two PLFs imaged from high‐resolution seismic records. A variety of geochemical methods are applied to study concentrations and types of gas, its character, and genesis. PLF 1 demonstrates ubiquitously low‐methane concentrations (14.2–55.3 ppm) that are likely due to partly unfrozen sediments with an ice‐saturated internal core reaching close to the seafloor. In contrast, PLF 2 reveals anomalously high‐methane concentrations of >120,000 ppm where frozen sediments are completely absent. The methane in all recovered samples is of microbial and not of thermogenic origin from deep hydrocarbon sources. However, the relatively low organic matter content (0.52–1.69%) of seafloor sediments restricts extensive in situ methane production. As a consequence, we hypothesize that the high‐methane concentrations at PLF 2 are due to microbial methane production and migration from a deeper source.